The bumbletown detectives : a problem-solving book. (Alexandria, Va. : Time-Life for Children, 1991)
Dame Edith and Sir Reginald decide to hire a detective to discover the thief at Mystery Manor, and the reader is encouraged to help with the clues.
Keywords: Mystery and detective stories